2021
DOI: 10.1101/2021.11.01.466778
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A universal, single primer amplification protocol (R-SPA) to perform whole genome sequencing of segmented dsRNA reoviruses

Abstract: BackgroundThe Reoviridae family represents the largest family of double-stranded RNA (dsRNA) viruses, and the members have been isolated from a wide range of mammals, birds, reptiles, fishes, insects, plants. Orthoreoviruses, one of the 15 recognized genera in the Reoviridae family, can infect humans and nearly all mammals, and birds. Genomic characterization of reoviruses has not been adopted on a large-scale due to the complexity of obtaining sequences for all 10 segments.ResultsIn this study, we developed a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…For this reason, only the strategies that included the R-SPA step were investigated in our subsequent experiments. The results obtained by applying only R-SPA to the samples (Figure 4, average of 14% ARV reads in a sample) were consistent with the results reported by Chrzastek et al [13]. However, we observed that R-SPA seemed to work better for the vaccine strain S1133 (~45% ARV reads) than it did for the clinical isolates (<11% ARV reads).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…For this reason, only the strategies that included the R-SPA step were investigated in our subsequent experiments. The results obtained by applying only R-SPA to the samples (Figure 4, average of 14% ARV reads in a sample) were consistent with the results reported by Chrzastek et al [13]. However, we observed that R-SPA seemed to work better for the vaccine strain S1133 (~45% ARV reads) than it did for the clinical isolates (<11% ARV reads).…”
Section: Discussionsupporting
confidence: 91%
“…The amplification of the ARV genetic content in a sample can be conducted via PCR amplification of the viral genome before NGS [ 24 , 25 ] or via target capture NGS [ 26 ]. While we are unaware of an available target capture NGS scheme with ARV-specific probes, early this year, Chrzastek and collaborators reported a single primer amplification assay (R-SPA) that significantly improved the recovery of ARV mapping reads after sequencing [ 13 ]. This approach was evaluated in the experiments documented herein, alone and in combination with the other ARV purification methods mentioned above.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations